Validity and reliability of the Dietary Sodium Restriction Questionnaire in peritoneal dialysis patients - Yunyao Lin; Ruolin Li; Zhihao Chen; Yingxin Xie; Junyan Fang; Pu Li; Mingzi Chu; Yingli Liu (PLoS ONE, 2025)
Objective The Chinese version of Dietary Sodium Restriction Questionnaire (DSRQ) was adapted to evaluate its reliability and validity for measuring adherence to a sodium-restricted diet in peritoneal dialysis (PD) patients. Methods Specific items related to peritoneal dialysis were added to create a PD version of the DSRQ (PD-DSRQ), which was administered to 135 patients undergoing PD. Item analysis was performed using the critical ratio and homogeneity tests. The reliability of the questionnaire was determined by assessing the internal consistency. Content validity was evaluated using the expert evaluation method, and construct validity was assessed via exploratory and confirmatory factor analyses. Results The item analysis revealed correlation coefficients (R-values) ranging from 0.311 to 0.745 for each item, with statistically significant differences between the high and low subgroups for all items. The Cronbach’s α coefficients for the overall PD-DSRQ and the attitude, subjective norm, and perceived behavioral control subscales were 0.805, 0.892, 0.794, and 0.889, respectively. The item-level content validity index ranged from 0.83 to 1.00, and the scale-level content validity index/universal agreement was 0.9894. Exploratory factor analysis identified a three-factor structure consistent with the original DSRQ, except for Question 18. The three factors had eigenvalues of 5.302, 4.179, and 1.290, which explained 64.32% of the variance. The average variance extracted for each dimension was 0.5777, 0.5654, and 0.5259, and the composite reliability values were 0.8864, 0.7956, and 0.8802, respectively, demonstrating good convergent and discriminant validity. Conclusion The PD-DSRQ encompasses general information and three dimensions: attitude, subjective norms, and perceived behavioral control. The questionnaire demonstrated strong reliability and validity, making it a reliable tool for assessing adherence to sodium-restricted diets in patients undergoing PD.